Pulmonary Visceral Pleura Biomaterial: Elastin- and Collagen-Based Extracellular Matrix - Lu, Xiao; Han, Ling; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: The goal of the study is to determine the structural characteristics, mechanical properties, cytotoxicity, and biocompatibility of the pulmonary visceral pleura (PVP). Background: Collagen and elastin are the major components of extracellular matrix. The PVP has abundance of elastin and collagen that can serve as a potential biomaterial for clinical repair and reconstructions. Methods: The PVP were processed from swine and bovine lungs. Chemical analyses were used to determine collage and elastin contents in the PVPs. Immunofluorescence microscopy was used to analyze the structure of the PVP. The stress-strain relationships and stress relaxation were determined by planar uniaxial test. The cytotoxicity of the PVP were tested in cultured cells. In in vivo evaluations, the PVP were implanted in the sciatic nerve and skin of rats. Results: Collagen and elastin contents are abundant in the PVP with larger proportions of elastin as compared to bovine pericardium and porcine small intestinal submucosa. A micro-structural analysis revealed that the elastin fibers distributed throughout the PVP and the collagen distributed mainly in the mesothelial basal lamina. The incremental moduli in stress-strain curves and relaxation moduli in Maxwell-Weichert model of PVP were approximately one tenth of bovine pericardium and small intestinal submucosa. The minimal cytotoxicity of the PVP was demonstrated. The axons proliferated in the PVP conduit guidance from proximal to distal sciatic nerves of rats. The neo-skin regenerated under the PVP skin substitute within 4 weeks. Conclusions: The PVP is comprised of abundant collagen and elastin. The structural characteristics and mechanical compliance of the PVP render a suitable biologic material for repair/reconstruction.